The role of NDRG1 in the pathology and potential treatment of human cancers. Issue 11 (8th June 2013) - Bae, Dong-Hun; Jansson, Patric J; Huang, Michael L; Kovacevic, Zaklina; Kalinowski, Danuta; Lee, C Soon; Sahni, Sumit; Richardson, Des R
Abstract : N-myc downstream regulated gene 1 (NDRG1) has been well characterised to act as a metastatic suppressor in a number of human cancers. It has also been implicated to have a significant function in a number of physiological processes such as cellular differentiation and cell cycle. In this review, we discuss the role of NDRG1 in cancer pathology. NDRG1 was observed to be downregulated in the majority of cancers. Moreover, the expression of NDRG1 was found to be significantly lower in neoplastic tissues as compared with normal tissues. The most important function of NDRG1 in inhibiting tumour progression is associated with its ability to suppress metastasis. However, it has also been shown to have important effects on other stages of cancer progression (primary tumour growth and angiogenesis). Recently, novel iron chelators with selective antitumour activity (ie, Dp44mT, DpC) were shown to upregulate NDRG1 in cancer cells. Moreover, Dp44mT showed its antimetastatic potential only in cells expressing NDRG1, making this protein an important therapeutic target for cancer chemotherapy. This observation has led to increased interest in the examination of these novel anticancer agents.